Foreign Languages and Aesopianisation: When the Popularity of Fables Unlocks Spanish - Safir, Kassim Boudjelal (Освітні виклики, 2024)
Purpose. This article explores the concept of the ‘Aesopianisation’ of other languages, focusing on the idea of using Aesop’s fables as a language learning aid. The fable of “The Fox and the Grapes” serves as an example of the widespread popularity of Aesop's timeless stories, making them an ideal resource to unlock related languages, such as Spanish.Methodology. The integration of beloved fables into reading comprehension and classroom discussion captivates students' imaginations and may help to solve one of the most daunting challenges in education: mastering analytical reading. Employing content analysis, this article delves into the application of narrative popularity effect (NPE) (1), linguistic context predictability (LCP) (2), lexical interlingual cognates (LIC) (3), and collocational patterns (CP) (4) as four useful linguistic tools to solve one of the most daunting educational challenges: unlocking a foreign language through detailed analytical reading. Results. The findings reveal a remarkable ability of these tools to extract the lexicon and structures from ten selected popular fables in Spanish, underscoring the potential efficacy of this approach in language learning.Conclusions. The study suggests that combining linguistic and cultural awareness can be a powerful tool for learning foreign languages, demonstrating that the ‘Aesopianisation’ of a language is indeed possible.